Pengaruh Kualitas Produk, Harga dan Promosi terhadap Minat Beli Produk Makrame (Studi pada Taritali Makrame) - Triyana Triyana; Rasistia Wisandianing Primadineska (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
Macrame craft is a form of craft that is being loved by interior design lovers. Because handicrafts are a unique product, it is necessary to know the things that influence a person’s buying interest in these products. This study aims to determine the effect of price, product quality and promotion on the intention to buy macrame products. The research data was collected using an online questionnaire which was distributed via social media. The samples used in this study are potential customers who have interacted with Taritali Macrame. Obtained a total sample of 100 respondents. The data analysis technique used is multiple linear regression analysis. The results of the study show that price, promotion and product quality influence purchase intention positively and significantly, especially for macrame craft products. Based on the test results of the coefficient of determination, it is 56.2% of the variable in this study that influences the intention to buy macrame craft products.